2010
DOI: 10.1105/tpc.109.066605
|View full text |Cite
|
Sign up to set email alerts
|

DAY NEUTRAL FLOWERING Represses CONSTANS to Prevent Arabidopsis Flowering Early in Short Days  

Abstract: The photoperiodic response in Arabidopsis thaliana requires the precise regulation of CONSTANS (CO) expression in relation to the light period during the day. In short days (SDs) levels of CO expression are normally low during the light period, and this results in delayed flowering compared with long days (LDs) when CO expression rises to high levels before the end of the light period. We identified a novel flowering time gene called DAY NEUTRAL FLOWERING (DNF) that acts in the same flowering pathway as CO. DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Previously, flowering-time mutants that are affected only under SD conditions have been reported. For example, phyB, dnf, spa1 and cop1 flower early, whereas vil1, vil2 and a gain-of-function mutation in IAA7/AXR2 (axr2-1) flower late specifically under SD conditions (Ishikawa et al, 2006;Kim and Sung, 2010;Laubinger et al, 2006;Mai et al, 2011;McNellis et al, 1994;Morris et al, 2010;Reed et al, 1993;Sung et al, 2006). However, vil1, vil2 and axr2-1 mutants display quantitative differences in flowering time compared with the wt and still flower under SD conditions (Kim and Sung, 2010;Mai et al, 2011;Sung et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, flowering-time mutants that are affected only under SD conditions have been reported. For example, phyB, dnf, spa1 and cop1 flower early, whereas vil1, vil2 and a gain-of-function mutation in IAA7/AXR2 (axr2-1) flower late specifically under SD conditions (Ishikawa et al, 2006;Kim and Sung, 2010;Laubinger et al, 2006;Mai et al, 2011;McNellis et al, 1994;Morris et al, 2010;Reed et al, 1993;Sung et al, 2006). However, vil1, vil2 and axr2-1 mutants display quantitative differences in flowering time compared with the wt and still flower under SD conditions (Kim and Sung, 2010;Mai et al, 2011;Sung et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are additional variations, including those with no ml histidines at all (RING-C2), proteins with Asp instead of Cys/ His at ml5 (RING-D), a few with ml residues replaced with Ser (RING-S/T such as found in DNF, DAY NEUTRAL FLOWERING, At3g19140) and others with a C4HC3 configuration combined with additional amino acids between ml4 and 5 (RINGv type). At least one member from each of these types was shown to be active as an E3 in vitro (Stone et al, 2005;Morris et al, 2010).…”
Section: The Ring Type E3s-general Commentsmentioning
confidence: 99%
“…Therefore, AthATL62/DFN may inhibit CO expression during SD, thereby preventing flowering. 43 GIGANTEA, FKF1 and CYCLING DOF FACTORS are factors that repress CO expression. It has been shown that AthATL62/DFN also functions in another regulatory pathway that activates CO. 20 …”
mentioning
confidence: 99%